NUDT15 R139C variation increases the risk of azathioprine-induced toxicity in Chinese subjects: Case report and literature review - Fei, Xiang; Shu, Qing; Hua, Bing-zhu; Wang, Shi-ying; Chen, Zhi-yong; Ge, Wei-hong; Fang, Yun (Medicine (Baltimore), 2018)
Azathioprine (AZA) is widely used as an immunosuppressive agent, and its efficacy has been recommended by many clinical studies. However, leukopenia, the most common toxicity, still restricts its clinical applications. Recent studies found that NUDT15 R139C polymorphism is strongly associated with AZA-induced leukopenia in Koreans. However, the follow-up studies available are all limited to inflammatory bowel disease (IBD). Here, we report a case of a Chinese patient with Sjögren syndrome (SS) with wild-type TPMT*3C who was diagnosed with AZA-induced severe toxicity due to NUDT15 mutation based on clinical and laboratory characteristics. A 22-year-old Chinese woman with SS developed severe leukopenia after AZA administration for 21 days. Detection of 6-thioguanine nucleotides (6-TGN) showed that the erythrocyte concentration had beyond the monitoring range, indicating that severe leukopenia might be caused by AZA. Furthermore, gene sequencing showed that NUDT15 R139C (poor metabolizer) homozygosity might explain this adverse event. Based on the evidence, AZA administration was immediately stopped and supportive treatments provided, and the patient eventually recovered. In this report, we first provide detailed clinical and laboratory characteristics of AZA-induced leukopenia in a patient with SS with a mutant NUDT15 R139C genotype (TT allele) and normal TPMT activity. This case indicates that NUDT15 R139C and TPMT*3C genotypes, and more importantly, 6-TGN levels, should be routinely monitored for those administered with AZA to predict and prevent AZA-induced toxicity.